Petrographic Characterisation and Paleoenvironmental Reconstruction of the Kipala Shales (Central Basin, DRC, Kwilu Province) - Munene, Djonive; Kanika Mayena, Thomas; Kimbungu Etumba , Elie; Makutu Mangwayaya , Adalbert-Jules; Dominique, Wetshondo Osomba; Nakasila Kinakow , Jules; Katakanga N’kembo , Audrey; Kabama Kasombo , Napoleon; Koy Kasongo, Ruben (Analecta Technica Szegedinensia, 2024)
In order to fill the glaring gaps in geological data for the Kipala region, in the Kwilu province of the Democratic Republic of Congo, geological studies were carried out. The results identified four different lithofacies in the study area: dark greasy shale, feldspathic microgres, clayey sandstone and bituminous shale. The petrographic compositions and palaeoenvironmental conditions of the deposit are presented for the first time in this work. From a petrographic point of view, the rock samples analysed differ in the nature of their constituent minerals and/or matrix or cement. Similarly, there is a close relationship between local lake and river sediments. The size and degree of rounding of the clayey sandstones in the rocks studied suggest that they were transported over a long period under strong hydrodynamic conditions.